2019
DOI: 10.16984/saufenbilder.472112
|View full text |Cite
|
Sign up to set email alerts
|

The influence of canola oil biodiesel on performance, combustion characteristics and exhaust emissions of a small diesel engine

Abstract: In this work, the influence of canola oil biodiesel addition to eurodiesel was evaluated on combustion, performance characteristics and exhaust emissions of a single cylinder diesel engine. In the experiments, fuel mixtures obtained by adding 10%, 20% and 50% canola oil biodiesel (named COB10, COB20 and COB50 respectively) to eurodiesel fuel (COB0) were used. The test engine was loaded at full load with electrical dynamometer and data was recorded between 1500 rpm and 3000 rpm at 500 rpm intervals. The result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ignition delay is one of the most significant elements in combustion characteristics and is defined as the time gap in crank angle degrees between the beginning of injection and the start of combustion [95]. Many researchers [50][51][52][94][95][96][97][98][99] discovered that with the use of biodiesel and its blends in diesel engines, the ignition delay is shorter than that of a diesel-fuelled engine. Gumus [94] investigated the combustion characteristics of a DICI engine running with diesel fuel, hazelnut kernel oil methyl ester (HOME) biodiesel, and blended fuel.…”
Section: Ignition Delay Idmentioning
confidence: 99%
See 2 more Smart Citations
“…Ignition delay is one of the most significant elements in combustion characteristics and is defined as the time gap in crank angle degrees between the beginning of injection and the start of combustion [95]. Many researchers [50][51][52][94][95][96][97][98][99] discovered that with the use of biodiesel and its blends in diesel engines, the ignition delay is shorter than that of a diesel-fuelled engine. Gumus [94] investigated the combustion characteristics of a DICI engine running with diesel fuel, hazelnut kernel oil methyl ester (HOME) biodiesel, and blended fuel.…”
Section: Ignition Delay Idmentioning
confidence: 99%
“…The reduction in ignition delay is caused by increasing the CN with higher biodiesel concentrations in blends with diesel fuel. According to certain researchers [96][97][98][99], the high CN of biodiesel had a significant influence on ignition delay. In comparison to diesel, Gnanasekaran [50] found that using biodiesel blends in diesel engines resulted in a shorter ignition delay.…”
Section: Ignition Delay Idmentioning
confidence: 99%
See 1 more Smart Citation